1992
DOI: 10.3892/ijo_00000044
|View full text |Cite
|
Sign up to set email alerts
|

The expression and prognostic value of ROCK I and ROCK II and their role in human breast cancer

Abstract: ΔROCKII vs. 18.4±1.4 control, p<0.001). Similarly, both exhibited reduced motility compared with control cells (p<0.001) and lost their response to HGF. Importantly, no significant difference existed between knockdown and control cells in in vivo tumour growth. ROCKI was significantly higher in human mammary tumours than normal background tissue (2.9±1.1 vs. 0.29±0.13, p=0.023), although expression of ROCKII was fairly consistent in both (2050±646 vs. 2303±2079). ROCKI expression was greater in patients who di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
84
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(98 citation statements)
references
References 0 publications
11
84
0
3
Order By: Relevance
“…Overexpression of the ROCK proteins has been implicated in the invasive and metastatic potential of various tumor types [9][10][11]. Baseline protein expression of ROCK1 and ROCK2 was higher in H1975 cells compared to H1650 and H358 NSCLC cells (Fig.…”
Section: Role Of Rho-associated Coiled Coil Forming Protein (Rock) Anmentioning
confidence: 99%
“…Overexpression of the ROCK proteins has been implicated in the invasive and metastatic potential of various tumor types [9][10][11]. Baseline protein expression of ROCK1 and ROCK2 was higher in H1975 cells compared to H1650 and H358 NSCLC cells (Fig.…”
Section: Role Of Rho-associated Coiled Coil Forming Protein (Rock) Anmentioning
confidence: 99%
“…Phosphorylation of the myosin II light chain triggers the contractile activity of myosin II (Narumiya et al, 2009). High levels of the myosin kinase Rho-associated protein kinase 1 (ROCK1) are associated with poor survival in breast cancer patients (Lane et al, 2008) and correlate with poor tumour differentiation, muscle invasion and lymph node metastasis in bladder cancer (Kamai et al, 2003). One clinical study showed a positive correlation between myosin light chain kinase, which activates myosin II, with disease recurrence and metastasis in non-small cell lung cancer (Minamiya et al, 2005).…”
Section: Cortexmentioning
confidence: 99%
“…ROCK is implicated in the regulation of breast cancer metastasis. A clinical study showed that increased expression of ROCK corresponds to late-stage tumors and metastases and is negatively correlated with overall survival in breast cancer patients (1). Overexpression of ROCK enhances invasion/migration in breast and other tumor cells in vitro (2,3).…”
Section: Introductionmentioning
confidence: 99%